Biodegradation in compost environment of PLA bioplastic containing brown algae biomass - IHAMOUCHEN, Chadia (Biopolymer Applications Journal, 2023)
This work was focused to the study of the biodegradation of poly lactic acid (PLA) alga composites in compost environment over a period of 50 days. To highlight the interaction between the natural reinforcement and the matrix, an in-situ grafting of maleic anhydride directly during the implementation in the extruder, will be consider to act as a compatibilizing agent (PLA-g-MAH) in the PLA/Algae system. The monitoring of the degradation process was evaluated by infrared structural analysis, mass loss and mechanical tensile analysis. The results revealed that the mass change is positive, suggesting that the chain scission phenomenon predominates over the cross-linking phenomenon. The mass loss increases with the loading rate, processing and composting time. The tensile test study revealed a decrease in stress and elongation and an increase in stiffness with the addition of the untreated filler. The treatment resulted in an improvement in mechanical properties. After 50 days in the compost medium, it was found that all the parameters underwent a clear decrease due to the chain scission reactions by enzymatic hydrolysis. For the FTIR results, an increase in the intensity of the O-H absorption band at 3325 cm-1 was observed with the untreated load, due to its high OH concentration. With treatment, this decreases, attributed mainly to the decrease in the hydrophilic character of the feed after treatment. After 50 days of composting, we have a decrease of the absorption band located at 1120 cm-1 (υ C-O) which corresponds to the hydrolysis of the ester bond. The appearance at 1620 cm-1 of a new band corresponds to the ends of carboxylic acid chains (COO) generated by enzymatic hydrolysis, due to microorganisms that consume lactic acid and surface oligomers